ORIENTASI TUJUAN MENYUSUN SKRIPSI DAN KECEMASAN DALAM MENULIS SKRIPSI - DEASYANTI DEASYANTI; MARWA NURUZDAH (Journal of Research and Measurement in Psychology, 2017)
The purpose of this study is to find out the relationship between thesis writing orientation and anxiety in thesis writing. Quantitative method is used in this study with 247 Universitas Negeri Jakarta students who is writing thesis as a samples. Sampling method used in this study is incidental sampling. The Instruments used in this study are adapted from Achievement Questionare Scale (Elliot & McGregor, 2001) and Writing Apprehension Test (Daly & Miller, 1975). Data analyzing method used in this study is pearson product moment. The goal orientations which is found negatively correlated with writing anxiety are mastery approach goal orientation (-0,31) and performance approach goal orientation (-0,18). The goal orientation which is found positively correlated with writing anxiety are mastery avoidance goal orientation (0,19) and performance avoidance (0,26).